2017
DOI: 10.1002/bip.23007
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms and domain/splice variants modulate assembly and elastomeric properties of human elastin. Implications for tissue specificity and durability of elastic tissue

Abstract: Polymeric elastin provides the physiologically essential properties of extensibility and elastic recoil to large arteries, heart valves, lungs, skin and other tissues. Although the detailed relationship between sequence, structure and mechanical properties of elastin remains a matter of investigation, data from both the full-length monomer, tropoelastin, and smaller elastin-like polypeptides have demonstrated that variations in protein sequence can affect both polymeric assembly and tensile mechanical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 76 publications
1
26
0
Order By: Relevance
“…1C). The stress relaxation of ELP 3 was greater than that of tropoelastin, but remains in the normal range for elastins and ELPs (41,42). Taken together, these data demonstrate that ELP 3 recapitulates the fundamental macroscopic properties of the monomeric, coacervated, and cross-linked forms of tropoelastin.…”
Section: Resultsmentioning
confidence: 70%
“…1C). The stress relaxation of ELP 3 was greater than that of tropoelastin, but remains in the normal range for elastins and ELPs (41,42). Taken together, these data demonstrate that ELP 3 recapitulates the fundamental macroscopic properties of the monomeric, coacervated, and cross-linked forms of tropoelastin.…”
Section: Resultsmentioning
confidence: 70%
“…21 Elastin dysfunction is associated with incompletely penetrant supravalvular aortic stenosis and other vascular lesions, none of which were found on examination using cardiac computed tomography. In the same participant, we detected a likely pathogenic frameshift variant in LZTR1, associated with increased risk for schwannomas.…”
Section: Personal Genome Sequencing and Medical Annotationmentioning
confidence: 99%
“…It has been shown that the insertion or deletion of TE domains or the mutation of certain amino acid residues affects diverse mechanisms associated with the assembly of TE monomers into a polymeric network such as coacervation and cross‐linking processes as well as the resultant mechanical properties. This suggests that variations in the TE sequence allow tissue‐specific alterations in elastin properties or are responsible for abnormal fiber formation under pathological conditions …”
Section: Tropoelastin Domain Structure and Expressionmentioning
confidence: 99%
“…This suggests that variations in the TE sequence allow tissue-specific alterations in elastin properties or are responsible for abnormal fiber formation under pathological conditions. [15][16][17] TE's sequence is highly repetitive and about 80% are composed of the four amino acids Gly, Ala, Val, and Pro. The precursor has alternating hydrophobic and more hydrophilic domains, which are encoded by individual exons, so that the domain structure of the protein is reflected in the exon organization of its gene.…”
Section: Introductionmentioning
confidence: 99%